Ethnolinguistic Study of Local Wisdom in Ex-Residency of Surakarta - Wakit Abdullah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This study discusses “the local wisdom summarized in the proverbs of the Javanese community in Ex-residency of Surakarta”. The purposes of this study are to describe (1) the background of the local wisdom as summarize in the proverbs of the Javanese community in Ex-residency of Surakarta, (2) to elaborate further reasons and specific times the people in Ex-residency of Surakarta employ the Javanese proverbs that summarize the local wisdom, and (3) explain the cultural meanings resided in the Javanese proverbs. This study employed ethnographic methods framed by the ethnolinguistic study to find the cultural meanings. Data and the data sources are categorized into primary and secondary data; the data collection method is done through the observation-participation and in-depth interview techniques; data analysis employed the ethnoscience model which underwent 12-phases of advanced research stages (of taxonomic, componential and domain analyses) to find the cultural themes; validity of the data is attested with the triangulation techniques (the triangulation of data, methods, researcher, and theory). The results encompassed (1) background of the local wisdom summarized in the Javanese proverbs expressed by the Javanese community in Ex-residency of Surakarta influenced by the cultural factors, the Javanese language, aesthetical, ethical, social, economical, political, and geographical factors; (2) the community in Ex-Surakarta expressed the Javanese proverb that summarizes local wisdom, the demands of fidelity to the culture is inevitable, media that facilitates the growth of the Javanese language, aesthetical and ethical motivations, social conditions, economical motivation, political media which show the geographical background; and (3) the cultural meaning of the Javanese proverbs which summarize the local wisdom of the community in Ex-residency of Surakarta, all of which are to show the courtesy, avoid direct confrontation, the proverbs also indicate levels of the beauty of the language use, nationalism, foster cooperation, develop the intellect.